Documenting the demise of tiger and leopard, and the status of other carnivores and prey, in Lao PDR's most prized protected area: Nam Et - Phou Louey - Rasphone, A; Kéry, M; Kamler, JF; Macdonald, DW (Elsevier, 2019)
The Nam Et - Phou Louey National Protected Area (NEPL) is known for its diverse community of carnivores, and a decade ago was identified as an important source site for tiger conservation in Southeast Asia. However, there are reasons for concern that the status of this high priority diverse community has deteriorated, making the need for updated information urgent. This study assesses the current diversity of mammals and birds in NEPL, based on camera trap surveys from 2013 to 2017, facilitating an assessment of protected area management to date. We implemented a dynamic multispecies occupancy model fit in a Bayesian framework to reveal community and species occupancy and diversity. We detected 43 different mammal and bird species, but failed to detect leopard Panthera pardus and only detected two individual tigers Panthera tigris, both in 2013, suggesting that both large felids are now extirpated from NEPL, and presumably also more widely throughout Lao PDR. Mainland clouded leopard Neofelis nebulosa had the highest estimates of probability of initial occupancy, persistence and colonization, and appeared to be the most widely distributed large carnivore, followed by dhole Cuon alpinus. Both of these species emerge as a priority for further monitoring and conservation in the NEPL landscape. This study provides the most recent assessment of animal diversity and status in the NEPL. Our analytical approach provides a robust and flexible framework to include sparse and inconsistent data sets of multiple species to assess their status via occupancy as a state process, which can often provide insights into population dynamics.